INNOVATIVE THERAPEUTIC STRATEGIES FOR MANAGING POST CASTRATION SYNDROME AFTER OVARIAN HYPERSTIMULATION (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
Definition and clinical importance Post‑castration syndrome (PCS) can develop after oocyte retrieval and luteal phase; severe ovarian hyperstimulation syndrome (OHSS) manifests as ascites, electrolyte imbalance, ovarian enlargement, and systemic signs. Although PCS is relatively rare, complications can be life-threatening and compromise IVF outcomes.